Aspekty chirurgicznego leczenia pacjenta z zespołem Klippela-Feila – opis przypadku = Surgical treatment aspects of the patient with Klippel-Feil syndrome – case report - Gnatek, Adrian; Szczepkowska, Aleksandra; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
Gnatek Adrian, Szczepkowska Aleksandra, Osica Piotr, Janas-Naze Anna. Aspekty chirurgicznego leczenia pacjenta z zespołem Klippela-Feila – opis przypadku = Surgical treatment aspects of the patient with Klippel-Feil syndrome – case report. Journal of Education, Health and Sport. 2016;6(11):137-146. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164437 http://ojs.ukw.edu.pl/index.php/johs/article/view/3973 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 02.11.2016. Aspekty chirurgicznego leczenia pacjenta z zespołem Klippela-Feila – opis przypadku Surgical treatment aspects of the patient with Klippel-Feil syndrome – case report Adrian Gnatek, Aleksandra Szczepkowska, Piotr Osica, Anna Janas-Naze Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail:pioosica@interia.pl Lek dent. Adrian Gnatek, lek.dent. Aleksandra Szczepkowska, dr n. med. Piotr Osica, dr hab.prof. Anna Janas-Naze Praca finansowana prze Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001 Streszczenie W artykule przedstawiono przypadek 12-letniej pacjentki poddanej leczeniu chirurgicznemu w znieczuleniu ogólnym. Słowa kluczowe: zespół Klippela-Feila, chirurgia, znieczulenie ogólne, ekstrakcja. Abstract The article shows the case of 12 years old patient, who was undergone surgical treatment in general anesthesia. Key words: Klippel-Feil syndrome, surgery, general anesthesia, extraction.